Intervención telefónica y competencia para cuidar de personas con enfermedad crónica - Gloria Mabel Carrillo González; Lizeth Adriana González Vega (Ciencia y Cuidado, 2018)
Objective: To determine the effect of a telephone intervention in people with a chronic disease to improve their profi ciency of care at home. Materials and Methods: Descriptive and exploratory study; 37 people with a chronic disease were enrolled, defi ned as cases, that came in to a health institution in Bogota. The telephone intervention was applied for a month after leaving the hospital, measurement of profi ciency was taken before and after for care at home and each telephone followup was registered to determine the perception of the users toward this intervention. Results: The majority of patients are males, with diagnoses of arterial hypertension, diabetes mellitus type II, chronic obstructive pulmonary disease- COPD, kidney failure and congestive heart failure, an average age of 66 years and domestic-work dedication. 100% of the sample has more than one chronic disease and low levels of dependency. The profi ciency to take care of, demonstrated medium levels before the beginning of the intervention, at the end it increased with signifi cant statistic changes. Regarding perception, this intervention is recognized as a continuity of care, relevant topics come up about the regulation of water consumption, medication administration and the diet, and an approach to emotional, social and economic components is demanded. Conclusions: The telephone intervention is an effective tool to increase the proficiency of care at home for people with a chronic disease, it generates a perception of safety, continuity and a bond with the health care team.